2006
DOI: 10.1111/j.1464-410x.2005.05962.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of alfuzosin 10 mg once daily: a 2‐year experience in ‘real‐life’ practice

Abstract: OBJECTIVETo assess the 2-year efficacy and safety of alfuzosin 10 mg once daily, a selective α 1 -adrenoceptor antagonist, in men complaining of lower urinary tract symptoms (LUTS) suggestive of benign prostate hyperplasia (BPH), in 'real life' practice. PATIENTS AND METHODSIn all, 839 European men with LUTS (mean age 67.3 years) were enrolled by general practitioners in a 2-year open-label study with alfuzosin 10 mg once daily. They were asked to complete the International Prostate Symptom Score (IPSS), its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
(74 reference statements)
6
25
0
1
Order By: Relevance
“…ED was reported in 65% of men, reduced ejaculate in 63% and painful ejaculation in 20%. There were significant improvements in weighted scores of all three variables after 1 year of alfuzosin (Figure 3), findings further confirmed by their group using the Brief Sexual Function Inventory questionnaire at 2-year follow-up [29].…”
Section: Management Of Luts/bph: Implications For Sdsupporting
confidence: 78%
“…ED was reported in 65% of men, reduced ejaculate in 63% and painful ejaculation in 20%. There were significant improvements in weighted scores of all three variables after 1 year of alfuzosin (Figure 3), findings further confirmed by their group using the Brief Sexual Function Inventory questionnaire at 2-year follow-up [29].…”
Section: Management Of Luts/bph: Implications For Sdsupporting
confidence: 78%
“…The long-term effectiveness of alfuzosin 10 mg once daily treatment in men with LUTS/BPH has been demonstrated in an open-label extension phase of a 3-month pivotal study (Van Kerrebroeck et al 2002), in a 2-year clinical-practice study (ALF-ONE; (Elhilali et al 2006)), and a 2-year study of BPH clinical progression (ALTESS; (Roehrborn 2006a)). In the ALFORTI pivotal study (Van Kerrebroeck et al 2002), patients randomized to receive alfuzosin 10 mg once daily or alfuzosin 2.5 mg 3 times daily during the double-blind phase received alfuzosin 10 mg for up to 9 months in the extension phase, whereas patients randomized to receive placebo during the double-blind phase received alfuzosin 10 mg for up to 9 months in the extension phase.…”
Section: Alfuzosin Clinical Efficacymentioning
confidence: 99%
“…In the ALF-ONE study (Elhilali et al 2006), in which the efficacy and safety of alfuzosin 10 mg once daily were evaluated in men with LUTS/BPH in a clinical-practice setting over a 2-year period, LUTS improved 39% and disease-specific quality of life improved 43% from baseline (both p < 0.0001; Table 2). The majority of men reported symptom relief within 2 weeks of treatment initiation that was maintained throughout the study.…”
Section: Alfuzosin Clinical Efficacymentioning
confidence: 99%
“…However, preliminary data suggest that treatment of the symptoms of BPH with some a-blockers may also improve ED and EjD. [33][34][35][36][37] Finally, data from a study of sildenafil suggested an improvement in LUTS in men being treated for ED. 38 As additional knowledge is gained on the mechanisms involved in the association between LUTS and SD, as well as other age-related diseases (e.g., hypertension, hyperlipidemia, diabetes mellitus and depression), 39 and as existing and new treatment options are evaluated, evidencebased management guidelines for these concomitant conditions should evolve.…”
Section: Physician Perceptions Of Sexual Dysfunction In Bphmentioning
confidence: 99%